Nephroprotective Effect of Dayak Onion (Eleutherine palmifolia) Against Monosodium Glutamate-Induced Renal Toxicity in Mice (Mus musculus) - Anggreani Desi Ramadhani Rahajeng; Aldin Akbar Rahmatullah; Cindy Ercha Aulia Putri; Rahmi Sugihartuti; Endang Suprihati; Hani Plumeriastuti; Mohammad Sukmanadi; Iwan Sahrial Hamid (Universitas Airlangga, 2024)
Background: The toxicological impacts of monosodium glutamate (MSG), a commonly used food additive, present a significant public health concern. Excessive MSG consumption will increase radical oxidative species, inducing a stress oxidative condition that ultimately results in kidney damage. Purpose: This study aimed to explore the nephroprotective effects of ethanol extracts from Dayak onion (Eleutherine palmifolia) against MSG-induced renal toxicity in mice (Mus musculus). Method: Twenty-five 11 week-old male mice, weighing approximately 20 g each, were divided into five research groups. Group C- received only CMC-Na 0.5%, Group C+ received 4000 mg/kg BW MSG, while Groups T1, T2, and T3 were administered 4000 mg/kg BW MSG along with Dayak onion extract at doses of 30 mg/kg BW, 60 mg/kg BW, and 120 mg/kg BW respectively. All treatments were carried out orally for 52 days. The mice were euthanized by cervical dislocation, and their kidneys were extracted for the examination of any histopathological changes. The data underwent analysis utilizing the Kruskal-Wallis test, followed by the Mann-Whitney test. Results: The results as indicated by the histopathological evaluation of the mice’s kidneys revealed significant improvements in the histo-architecture of the kidneys. Supplementation of Dayak onion extract in mice induced with MSG decreased the degeneration and necrosis of the tubule epithelium, and it also repaired the glomerular necrosis. Conclusion: Oral administration of Dayak onion extract to mice exposed to monosodium glutamate demonstrated a notable reduction in kidney damage and helped maintain renal health significantly.